1975
DOI: 10.1042/bj1490547
|View full text |Cite
|
Sign up to set email alerts
|

The pH-dependence and group modification of β-lactamase I

Abstract: The pH-dependence of the kinetic parameters for the hydrolysis of the beta-lactam ring by beta-lactamase I (penicillinase, EC 3.5.2.6) was studied. Benzylpenicillin and ampicillin (6-[D(-)-alpha-aminophenylacetamido]penicillanic acid) were used. Both kcat. and kcat./Km for both substrates gave bell-shaped plots of parameter versus pH. The pH-dependence of kcat./Km for the two substrates gave the same value (8.6) for the higher apparent pK, and so this value may characterize a group on the free enzyme; the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…The pH profiles of the steady-state kinetic parameters k cat ͞K M and k cat are approximately bell-shaped with ratecontrolling ionization constants pK a1 and pK a2 centered on values of Ϸ 4.4 and Ϸ 8.2, respectively (8)(9)(10)(11)(12). It has been suggested that K73 is uncharged in TEM-1 ␤-lactamase and functions as the proton acceptor (4,13).…”
mentioning
confidence: 97%
“…The pH profiles of the steady-state kinetic parameters k cat ͞K M and k cat are approximately bell-shaped with ratecontrolling ionization constants pK a1 and pK a2 centered on values of Ϸ 4.4 and Ϸ 8.2, respectively (8)(9)(10)(11)(12). It has been suggested that K73 is uncharged in TEM-1 ␤-lactamase and functions as the proton acceptor (4,13).…”
mentioning
confidence: 97%
“…Previous studies had demonstrated rapid inactivation of ~-lactamase I in the presence of a water soluble carbodiimide (37). In the current investigation, taurine was used to convert the reactive O-acylisourea intermediate (formed during the reaction of DCC with carboxyls) to a stable amide derivative.…”
Section: Dicarboxylic Amino Acidsmentioning
confidence: 97%
“…Earlier attempts using enzymatic and chemical methods have failed to reveal any C-terminal residue in ~-lactamase I (35,37). The broad specificity of carboxypeptidase Y as well as its resourcefulness as an agent in the elucidation of the amino acid sequence of the C-terminal region of proteins (17,26) prompted us to reinvestigate the nature of the C-terminal residue of ~-lactamase I.…”
Section: C-terminal Amino Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The design as well as the kinetic parameters used in computing curve b in Figure 5 and the profiles in Figure 6b are those corresponding to the penicillinase-pH electrode developed by Nilsson et al (1973) for monitoring penicillin-G. From the thickness of the membrane used in their experiments, the enzyme loading of their membrane, and the kinetic parameters of penicillinase (Waley, 1975) we computed that the experimental electrode of Nilsson et al had a Thiele modulus of 18.8. In their experiments, Nilsson et al maintained the bulk solution a t the optimal pH of the enzyme and investigated the electrode response in the presence of 5 x lo-, M sodium phosphate buffer for bulk substrate concentrations ranging from 5 x to 1 x M. As was already noticed from Figure 6b, under these conditions f + 1 for the entire range of substrate concentrations investigated by these authors.…”
Section: Case 2 Enzymic Reaction Produces a Weak Acid Withmentioning
confidence: 99%